2004
DOI: 10.1051/0004-6361:20034155
|View full text |Cite
|
Sign up to set email alerts
|

The origin of H I-deficiency in galaxies on the outskirts of the Virgo cluster

Abstract: Abstract. Spiral galaxies that are deficient in neutral hydrogen are observed on the outskirts of the Virgo cluster. If their orbits have crossed the inner parts of the cluster, their interstellar gas may have been lost through ram pressure stripping by the hot X-ray emitting gas of the cluster. We estimate the maximum radius out to which galaxies can bounce out of a virialized system using analytical arguments and cosmological N-body simulations. In particular, we derive an expression for the turnaround radiu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
145
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(158 citation statements)
references
References 28 publications
12
145
1
Order By: Relevance
“…Cetus and Tucana) are likely systems that previously interacted with either the Milky Way or M31 (i.e. "backsplash" or "super-virial" galaxies, Mamon et al 2004, Wetzel et al 2014. This broadly agrees with our observations of low-mass isolated systems as well as the results of Geha et al (2012).…”
Section: Comparison To Previous Studiessupporting
confidence: 88%
“…Cetus and Tucana) are likely systems that previously interacted with either the Milky Way or M31 (i.e. "backsplash" or "super-virial" galaxies, Mamon et al 2004, Wetzel et al 2014. This broadly agrees with our observations of low-mass isolated systems as well as the results of Geha et al (2012).…”
Section: Comparison To Previous Studiessupporting
confidence: 88%
“…Bahé et al 2013). To address this, we also show pre-processing results for our 'strict' infall sample (2 < R < 3 R 200 ) which should be less susceptible to backsplash contamination, as many previous studies have shown that the majority of backsplashing galaxies are found within two virial radii (Mamon et al 2004;Mahajan et al 2011;Oman et al 2013;Haines et al 2015). If contamination from backsplash galaxies is low, this field excess should approximate the fraction of galaxies which have been pre-processed prior to infalling onto their present-day group.…”
Section: Galaxy Properties At Large Radiimentioning
confidence: 88%
“…Our analysis shows that most of the galaxies located at the position of the bump at a given redshift, are also positioned in the region of the bumps in later outputs. This finding leads us to rule out the possibility of rebound galaxies (Mamon et al 2004;Gill et al 2005;Mamon 2006) being the cause of the bump since these galaxies are expected to dramatically change their positions with respect to the group centre between redshifts 0.69 and 0.00. The apparent movement of the bump could therefore be the result of either infalling substructure or simply the growth of the virial radii of the systems concerned, i.e.…”
Section: The Apparent Movementmentioning
confidence: 98%